2012
DOI: 10.1194/jlr.m021030
|View full text |Cite
|
Sign up to set email alerts
|

Choline phosphorylation and regulation of transcription of choline kinase α in hypoxia

Abstract: by choline kinase to form phosphocholine is the fi rst step of multistep Kennedy pathway ( 1 ) that synthesizes the major membrane phospholipid, phosphatidylcholine. Increased choline phosphorylation (primarily by choline kinase ␣ , ChK ␣ ) in tumor as compared with normal tissue has been reported in lung, breast, colorectal, and prostate cancers ( 2-5 ). This has motivated evaluation of cancer therapies involving choline kinase inhibition ( 6 ) and use of cancer imaging techniques with choline phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…glucose and pyruvate) decreased in serum. Increased choline level might indicate that the serum milieu suffered severe hypoxia, resulting in a decreased choline kinase activity and choline phosphorylation . Leucine has been known as an activator of mTOR (mammalian target of rapamycin) signaling, which regulates diverse immune cells including neutrophils, mast cells, natural killer cells, macrophages, dendritic cells, T cells, and B cells .…”
Section: Resultssupporting
confidence: 59%
“…glucose and pyruvate) decreased in serum. Increased choline level might indicate that the serum milieu suffered severe hypoxia, resulting in a decreased choline kinase activity and choline phosphorylation . Leucine has been known as an activator of mTOR (mammalian target of rapamycin) signaling, which regulates diverse immune cells including neutrophils, mast cells, natural killer cells, macrophages, dendritic cells, T cells, and B cells .…”
Section: Resultssupporting
confidence: 59%
“…However Bansal et al have reported a decrease in choline phosphorylation in hypoxic prostate cancer cells which may result from other isoforms of hypoxia response elements (HRE) affecting ChoK activity in human brain tumors. There is intensifying urgency to find new drugs for the treatment of brain tumors (47). Development of anticancer agents is the key focus of several research studies on developing specific molecular targets against the malignant phenotype (5, 48, 49) with the ultimate goal of improving activity and therapeutic selectivity for tumor versus normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…This hepatotoxin was later found to cause upregulation of the oncogenic transcription factor c-jun that binds to an activator protein 1 (AP1) element site in the promoter region of CHKA [53]. Hypoxia response elements (HREs) in the CHKA promoter region have linked HIF1α activity to ChoKα expression [54,55]. Inhibitors of the mitochondrial electron transport chain in neuroblastoma cells can increase ChoKα expression and phospholipase activity, leading to elevated choline metabolites [56].…”
Section: Choline Kinasementioning
confidence: 99%